Health Related Quality of Life and its Predictors among Dyslipidemia Patients: A Cross-Sectional Study - Bhandari, Ramesh; Ganachari, Madiwalayya Shivkantayya (International Journal of Pharmaceutical Investigation, 2025)
Objectives To evaluate Health-Related Quality of Life (HRQoL) and its determinants among dyslipidemia patients. Materials and Methods A cross-sectional study was conducted among patients with dyslipidemia during 6 months at a tertiary care hospital. We included adult patients admitted to the hospital diagnosed with dyslipidemia also no restrictions were imposed whether the patients had complications of dyslipidemia. 36-Item Short Form Survey (SF-36) was used to calculate HRQoL. Multivariable generalized linear regression was used to identify associated factors. Results The overall Health-Related Quality of Life was found to be 52.52±14.35. Role limitations due to physical health, emotional health, social functioning and pain were the subdomains where the mean scores were less than half. Age was a negative predictor, while primary, secondary, higher secondary and graduate levels of education were positive predictors of Health-Related Quality of Life among dyslipidemia patients. Conclusion Findings from this study suggest that, despite a decrease in overall Health-Related Quality of Life (HRQoL), the lowest scores were observed in role limitations due to physical health, emotional health, social functioning and pain. Age and educational level significantly influence Health-Related Quality of Life among dyslipidemia patients.
Keywords: Drug utilization study; Dyslipidemia; Functional disability; Physical fitness; Quality of life